Cerebellar Cathodal Transcranial Direct Stimulation and Performance on a Verb Generation Task: A Replication Study. (14th February 2017) - Spielmann, K.; van der Vliet, R.; van de Sandt-Koenderman, W. M. E.; Frens, M. A.; Ribbers, G. M.; Selles, R. W.; van Vugt, S.; van der Geest, J. N.; Holland, P.
Abstract : The role of the cerebellum in cognitive processing is increasingly recognized but still poorly understood. A recent study in this field applied cerebellar Transcranial Direct Current Stimulation (c-tDCS) to the right cerebellum to investigate the role of prefrontal-cerebellar loops in language aspects of cognition. Results showed that the improvement in participants' verbal response times on a verb generation task was facilitated immediately after cathodal c-tDCS, compared to anodal or sham c-tDCS. The primary aim of the present study is to replicate these findings and additionally to investigate possible longer term effects. A crossover within-subject design was used, comparing cathodal and sham c-tDCS. The experiment consisted of two visits with an interval of one week. Our results show no direct contribution of cathodal c-tDCS over the cerebellum to language task performance. However, one week later, the group receiving cathodal c-tDCS in the first visit show less improvement and increased variability in their verbal response times during the second visit, compared to the group receiving sham c-tDCS in the first visit. These findings suggest a potential negative effect of c-tDCS and warrant further investigation into long term effects of c-tDCS before undertaking clinical studies with poststroke patients with aphasia.